Wpływ warunków geotechnicznych na awaryjność systemów odwodnień = The impact of geotechnical conditions on failure rate in water drainage systems - Kołodziejczyk, Urszula; Kołodziejczyk, Wiktor; Kuroczycki, Lech; Ogiołda, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water drainage systems costruction in area of low sTable geotechnical conditions could result in serious constructions emergencies both - drainage systems and adjoining buildings. Designed storm water system in Świebodzin (Lubuskie Province) in area of Łąki Zamkowe street is an example.
Keywords: warunki geotechniczne; awarie budowlane; klimat; geotechnical conditions; construction emergencies; climate